Modeling a cross-country skiing mass-start event using the W'balance model - Kocbach. J.; Mentzoni, F.; Losnegard, T.; Sandbakk, Ø. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: A main difference in cross-country skiing mass-start events compared to individual time-trial events is the possibility to reduce energy expenditure when drafting behind other skiers in packs. In the present study, we model a mass-start event based on the W` balance model and compare the models results with GNSS measurements. This model aims to provide insight into 1) the reasons for race evolvement and pack formation in mass-start events, 2) the corresponding physiological demands, and 3) why different athlete characteristics can lead to success in such events.